A influência das informações pictoriais e textuais no processo de compra de moda em ambiente on-line - Mattos, Luiza Tari Manzini Ferreira (2020)
Submitted by Adriana Alves Rodrigues (aalves@espm.br) on 2020-11-09T19:03:28Z No. of bitstreams: 1 LUIZA TARI MANZINI FERREIRA MATTOS.pdf: 3041744 bytes, checksum: 1643f434b98d5d00c1fcfa5811d3ab7d (MD5)